How does same-day-delivery online shopping reshape social interactions among neighbors in Nanjing?. (July 2021) - Xi, Guangliang; Cao, Xinyu; Zhen, Feng
Abstract: Local store shopping is a catalyst for social interactions among neighbors. As same-day-delivery (SDD) online shopping replaces local store shopping, it may reshape this social process through various mechanisms. However, few studies empirically explore the changes in these interactions. Using household survey data in Nanjing, this paper employs a structural equations model to explore the relationships among SDD online shopping, local store shopping, and three types of social interactions among neighbors. SDD online shopping is negatively associated with greeting/chatting with neighbors, but has a positive association with social gathering. Although SDD online shopping is positively associated with companion shopping with neighbors, the association is weaker than that between local store shopping and companion shopping. Therefore, SDD online shopping transforms neighborhood social interactions by weakening weak ties and strengthening strong ties with neighbors, undermining community vitality and social cohesion. Policies and programs should be developed to sustain neighborhood social interactions. Highlights: Same-day-delivery (SDD) online shopping reduces greeting/chatting with neighbors. SDD online shopping increases social gathering with neighbors. SDD online shopping has a weaker impact on companion shopping than local shopping. SDD online shopping undermines community vitality and social cohesion.